Da "chuva atípica" à "falta de todo mundo": a luta pela classificação de um desastre no município de Teresópolis / RJ - Vargas, Maria Auxiliadora Ramos (2013)
Disaster is a current and complex subject. The most common way in which this subject has been interpreted and widely advertised presents it with underlying objective and unique aspects in the social imaginary. This approach is supported primarily on discursive strategies and practices produced by a specific rationality than can be found in some institutions (and their representatives) who has the power to present a definition and promote intervention in the phenomenon that is disaster authorities . However there are evidences pointing out that disaster is not consolidated into a single representation. Instead it represents a force field made by multiple agents and interpretations, developed through different positions and rationalities, expressing tensions, disputes and classification struggle. Identify and discuss this particular field through sociological analysis noticing those institutionally situated actors and those who compose social groups that are directly affected is the main purpose of this work a qualitative research with the following methodological procedures: a literature review in Sociology and related areas, documentary collection and analysis, in-depth interviews. This thesis highlights the disaster in the city of Teresópolis/RJ as an important example of classification struggle and gets us close to vulnerability and abandonment processes concerning some specific social groups. It reveals power relations where there is an attempt at imposing monophonically scientific and technical knowledge to the detriment of popular culture which comes from life courses, in place experiences and past relation with threatening factors in an effort to attest diversity failure. However, multiple expressions of resilience among people affected by disaster are evidence of both the attempt to prevent them from speaking and the acknowledgement of a struggle in order to make their voices heard so that they become real participants in this political game and guarantee their condition as subjects of rights.